Management of the Mosque's Emirate in increasing Community Participation in Religious Activities (Study on the Jami' Baiturrahman Mosque, Olean Village, Situbondo Regency) - Khoiriyah, Rofidatul; Slamet, Slamet; Johanna, Anne; Avinash, Buschhaus (Journal International Dakwah and Communication, 2021)
Management is organizing, managing, and managing to achieve goals. The Imamate of the mosque is an effort so that the mosque institution can work as expected, namely as a center of worship, empowerment and unity of the people in order to improve ways, piety, noble character, intelligence of the people and the achievement of a just and prosperous society that is blessed by Allah SWT. The purpose of this research is to find out; How is the implementation of the management of the Jami' Baiturrahman mosque in increasing community participation in religion in Olean Village, Situbondo Regency. The method used in this study is a descriptive qualitative approach. Data collection techniques in this study using observation, interviews and documents. Data analysis techniques in this study used data reduction, data presentation and drawing conclusions. The data validity technique in this study uses triangulation of data sources and techniques. The results of this study indicate that the management of the mosque's Emirate in increasing community participation has been carried out to the maximum, because the mosque's administrators have implemented the theory of mosque's Emirate management starting from managing the management structure, religious activities, establishing active communication and expanding communication networks.